SELECTION OF NEW CULTURES OF LACTATE MICROORGANISMS AND STUDY OF THEIR PROPERTIES (Experimental biology, 2016)
This article deals with the isolation of lactic mikroorganizov from different natural sources and milk products. From milk products, as well as from the rhizosphere of plants and filo was isolated and analyzed in 38 strains of lactic microorganisms. Microorganisms isolated from shubat mainly represented coccoid forms. For complex traits studied (osmotolerantnosti fermenting ability, proteolytic and antibiotic activity) selected two active strain. It was found that the strains isolated bakteriotsinpodobnye substances depressing the test microorganism growth. Two active shtammmov studied the physiological and biochemical properties and the analysis of the nucleotide sequence of genes 16S rRNA. AYU13 strain is related to mind Lactobacillus paracasei, and strain AYU19 defined as Lactobacillus casei.
Keywords: lactic acid bacteria; shubat; proteolytic activity; antagonistic activity; test organisms.